Conducting Polymer-Mixed Oxide Composite Electrocatalyst for Enhanced Urea Oxidation. Issue 15 (1st January 2018) - Atta, Nada F.; El-Sherif, Rabab M. A.; Hassan, Hagar K.; Hefnawy, Mahmoud A.; Galal, Ahmed
Abstract : Considerable interest in urea electrooxidation reaction has developed recently because of possible generation of hydrogen and in direct urea fuel cell applications. Nickel and nickel-containing catalysts are the preferred electrode materials because of their efficient activity for this reaction. This work investigates a novel platform composed of a conducting poly(aniline) modified with lanthanum-nickel-based oxides/reduced graphene oxide as an electrocatalyst for urea electrooxidation in alkaline medium. The catalyst was prepared using a one-step and energy-saving procedure with graphene oxide as a substrate. The glassy carbon electrode modified with this catalyst exhibits an exceptional high specific current activity of 342 mA mg −1 cm −2 in 0.33 M urea/1.0 M KOH and reaches 615 mA mg −1 cm −2 in 0.33 M urea/3.0 M KOH. The catalyst was studied using cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy showing long term stability and resistance against fouling. The structure and morphology of the resulting material was characterized with XRD, SEM and EDAX analyses.